Therapeutic Options in Patients with Traumatic Splenic Injury - Dong Yeon Kang; Ji Woong Yeom; Young Goun Jo; Yun Chul Park; Wu Seong Kang; Jung Chul Kim (Journal of Acute Care Surgery, 2016)
Purpose Splenic injury management has shifted to non-surgical treatment to preserve the spleen because of the postoperative risks of overwhelming post-splenectomy infection. In this study, we analyzed risk factors of therapeutic options for splenic injury, using medical records of Chonnam National University Hospital. Methods We reviewed the medical records of 110 consecutive patients with traumatic splenic injuries admitted from January 2009 to December 2013. Demographic characteristics and therapeutic options such as conservative treatment, angiographic embolization and emergency operation and clinical parameters were analyzed in this study. Results Thirty-four patients were treated surgically and seventy-six were managed with non- surgical treatment. Multivariate logistic regression identified age (odds ratio [OR], 1.04; 95% confidence interval [CI], 1.009∼1.072; p=0.01), hematocrit (OR, 0.878; 95% CI, 0.806∼0.957; p=0.003), contrast extravasation (OR, 7.644; 95% CI, 2.248∼25.986; p=0.001), spleen grade (OR, 2.08; 95% CI, 1.128∼ 3.836; p=0.019) as significant risk factors of emergent splenectomy. Conclusion Age, hematocrit, contrast extravasation, spleen grade were significant risk factors for emergent splenectomy.